Fetal bovine serum: how to leave it behind in the pursuit of more reliable science - Weber, Tilo; Malakpour-Permlid, Atena; Chary, Aline; D’Alessandro, Vito; Haut, Leah; Seufert, Sebastian; Wenzel, Esther Veronika; Hickman, James; Bieback, Karen; Wiest, Joachim; Dirks, Wilhelm Gerhard; Coecke, Sandra; et al. (Frontiers in Toxicology, 2025)
Cell cultures form the backbone for scientific research and development, but also for clinical diagnostics and biotechnology. Supplying cells in vitro with growth factors, hormones, and other nutrients is achieved most often by supplementing culture media with fetal bovine serum (FBS). Despite its nearly ubiquitous use, there are major reproducibility, safety, and animal welfare issues arguing the need to replace FBS. Fortunately, numerous FBS replacements have been validated and are publicly or commercially available, making it possible to leave FBS behind. Successful serum-free, animal-component-free, and chemically defined media applications are highlighted in this review for the cultivation of stem cells and organoids, the development of organ-on-a-chip systems, the bioprinting of tissues, and the production of cultivated meat, antibodies, and vaccines, including the conduct of cytotoxicity tests and the cryopreservation of cells. Moreover, the use of fully animal-free models and methodologies is further discussed to promote their broader acceptance and adoption within the global scientific research and development community. In this regard, this review discusses novel avenues to address the scientific and practical hurdles that might limit a full transition from FBS to fully defined cell culture media and offers a brief perspective on potential future directions.